De Novo Transcriptome Dataset Generation of the Swamp Buffalo Brain and Non-Brain Tissues. (12th October 2022) - Xiaobo, Wang; Hassan, Faiz-ul; Liu, Sheng; Yang, Shuli; Ahmad, Muhammad; Ahmed, Ishtiaq; Huang, Kongwei; Iqbal, Hafiz M. N.; Yu, Hui; Liu, Qingyou; Rehman, Saif ur
Abstract : The sequenced data availability opened new horizons related to buffalo genetic control of economic traits and genomic diversity. The visceral organs (brain, liver, etc.) significantly involved in energy metabolism, docility, or social interactions. We performed swamp buffalo transcriptomic profiling of 24 different tissues (brain and non-brain) to identify novel transcripts and analyzed the differentially expressed genes (DEGs) of brain vs. non-brain tissues with their functional annotation. We obtained 178.57 Gb clean transcriptomic data with GC contents 52.77%, reference genome alignment 95.36%, exonic coverage 88.49%. Totally, 26363 mRNAs transcripts including 5574 novel genes were obtained. Further, 7194 transcripts were detected as DEGs by comparing brain vs. non-brain tissues group, of which 3, 999 were upregulated and 3, 195 downregulated. These DEGs were functionally associated with cellular metabolic activities, signal transduction, cytoprotection, and structural and binding activities. The related functional pathways included cancer pathway, PI3k-Akt signaling, axon guidance, JAK-STAT signaling, basic cellular metabolism, thermogenesis, and oxidative phosphorylation. Our study provides an in-depth understanding of swamp buffalo transcriptomic data including DEGs potentially involved in basic cellular activities and development that helped to maintain their working capacity and social interaction with humans, and also, helpful to disclose the genetic architecture of different phenotypic traits and their gene expression regulation.